The new world disorder challenges and threats in an uncertain world - Black, J. L. (Joseph Laurence), 1937-; Johns, Michael, 1974-; Theriault, Alanda (Lexington Books, 2019)
"This book describes and analyzes the source and nature of the phenomena that characterize new world disorder. These include domestic political crises with international consequences, disruptive regions, terrorism, climate change, deglobalization, and exponentially growing refugee movements"--